My emotions expressed by music - De Jong, Elske (2014)
Improvisational psychodynamic music therapy (IPMT) has been demonstrated by Erkkilä et al. (2011) to be effective in the treatment for people suffering from depression. For the purpose of a mixed methods research design all musical improvisations have been captured electronically, the therapist’s notes have been standardized, and the sessions have been recorded and saved. Furthermore, the research team of the university of Jyväskylä has developed a computational analysis software, called Music Therapy Toolbox (MTTB). The purpose of this master’s thesis was to investigate two improvisations from one case in-depth, through the use of the MTTB software. The findings are presented, as well as the analysis process. The main outcome produced 10 descriptive codes that are useful for analyzing MTTB graphs. The discussion has been presented in a separate chapter, connecting various theoretical concepts and principles from IPMT to the current data and findings. Theoretical topics of interest were; emotional content, depression and the expression of anger, symbolic meaning, severity of depression, emotion regulation and rumination, musical communication and the therapeutic relationship, and the limitations and advantages of microanalysis and MTTB.